Unmasking the silent threat: deep tissue impacts of chemical burns – a case report - Satbir S.G.; Fatimah Mat Johar; Ahmad Sukari Halim; Wan Azman Wan Sulaiman (Burns Open)
Chemical burns, often caused by corrosive substances like sulfuric acid, can result in severe physical and psychological harm. These injuries are challenging to manage due to difficulties in assessing burn depth and ongoing tissue damage beneath the eschar. This case report details a 21-year-old female with 9 % total body surface area full-thickness chemical burns from a battery acid assault affecting her face, chest, limbs, and eyes. Initial treatment included irrigation and pH monitoring, followed by early tangential excision, hydrosurgery, and skin allograft application. While surface eschar pH normalized after irrigation, subeschar tissue remained acidic, indicating deeper damage. The patient developed hypertrophic scarring, reflecting ongoing tissue damage beyond the visible eschar. Persistent subeschar acidity suggests that current treatment protocols may not sufficiently address the penetration of corrosive substances, leading to prolonged inflammatory processes and unfavorable scarring outcomes. This underscores the need for improved strategies to prevent prolonged inflammation and unfavorable outcomes in chemical burn management.